Summation of Fourier-Laplace Series in the Space $L(S^m)$ - Lasuriya, R. A. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We establish estimates of the rate of convergence of a group of deviations on a sphere in the space $L(S^m),\quad m > 3$.